ATP-induced Ca(2+)-signalling mechanisms in the regulation of mesenchymal stem cell migration - Jiang, Lin-Hua (Cell Mol Life Sci, 2017)
The ability of cells to migrate to the destined tissues or lesions is crucial for physiological processes from tissue morphogenesis, homeostasis and immune responses, and also for stem cell-based regenerative medicines. Cytosolic Ca(2+) is a primary second messenger in the control and regulation of a wide range of cell functions including cell migration. Extracellular ATP, together with the cognate receptors on the cell surface, ligand-gated ion channel P2X receptors and a subset of G-protein-coupled P2Y receptors, represents common autocrine and/or paracrine Ca(2+) signalling mechanisms. The P2X receptor ion channels mediate extracellular Ca(2+) influx, whereas stimulation of the P2Y receptors triggers intracellular Ca(2+) release from the endoplasmic reticulum (ER), and activation of both type of receptors thus can elevate the cytosolic Ca(2+) concentration ([Ca(2+)](c)), albeit with different kinetics and capacity. Reduction in the ER Ca(2+) level following the P2Y receptor activation can further induce store-operated Ca(2+) entry as a distinct Ca(2+) influx pathway that contributes in ATP-induced increase in the [Ca(2+)](c). Mesenchymal stem cells (MSC) are a group of multipotent stem cells that grow from adult tissues and hold promising applications in tissue engineering and cell-based therapies treating a great and diverse number of diseases. There is increasing evidence to show constitutive or evoked ATP release from stem cells themselves or mature cells in the close vicinity. In this review, we discuss the mechanisms for ATP release and clearance, the receptors and ion channels participating in ATP-induced Ca(2+) signalling and the roles of such signalling mechanisms in mediating ATP-induced regulation of MSC migration.